ANALYSIS OF DIFFERENCE SMEs REVENUE BEFORE AND AFTER PEOPLE BUSINESS CREDIT PROGRAM (KUR) BANK BRI UNIT PARE - Atmaja, Rizky Dwi Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Small Medium Enterprises (SMEs) have a very important role in the Indonesian economy which can be seen from the contribution of SMEs to gross domestic product, and the large number of SMEs business units scattered throughout Indonesia. Becausethese problems, the government provides facilities in the form of distribution of the People's Business Credit (KUR). The government took the initiative to establish the real sector, Under this program, SMEs can make loans with the guarantee borne by the government. To distribute them efficiently lending, the government appointed six government banks are BRI, BNI, BTN, Bank Mandiri, and Bank Bukopin as executor. People's Business Credit (KUR) is a program launched by the government in order to help SMEs productive and viable and bankable to have access to credit or financing from the Bank. To bridge the needs of SMEs in accessing banking, the government issued Presidential Decree No. 6 of 2007 on the Acceleration of Development of SMEs Sectorand Empowerment. In this case researchers used descriptive quantitative research, Interest authors used a quantitative approach is trying more extensive research in how to interpret the data that has been analyzed and the results of the analysis associated with the theories that have been there for then drawn a conclusion. Quantitative analysis is to analyze the revenue of SMEs before and after KUR in Pare district with Z test analysismethod.Keywords:Â Credit, Peopleâ€™s Business Credit, Revenue, Small Medium Enterprises